2013
DOI: 10.1088/0004-637x/768/1/71
|View full text |Cite
|
Sign up to set email alerts
|

New Constraints on Cosmic Reionization From the 2012 Hubble Ultra Deep Field Campaign

Abstract: Understanding cosmic reionization requires the identification and characterization of early sources of hydrogenionizing photons. The 2012 Hubble Ultra Deep Field (UDF12) campaign has acquired the deepest infrared images with the Wide Field Camera 3 aboard Hubble Space Telescope and, for the first time, systematically explored the galaxy population deep into the era when cosmic microwave background (CMB) data indicate reionization was underway. The UDF12 campaign thus provides the best constraints to date on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
756
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 558 publications
(810 citation statements)
references
References 137 publications
(270 reference statements)
50
756
4
Order By: Relevance
“…In our simulations, reionization completes at higher redshifts than suggested by constraints on the neutral fraction from observations of Lyman-α emitting galaxies and high-redshift quasars (e.g., Figure 5 in Robertson et al 2013). However, interpretations of these observations are dominated by large systematic uncertainties (for a discussion see, e.g., Robertson et al 2013;Jensen et al 2013;Dijkstra 2014;Mesinger et al 2014;Taylor & Lidz 2014).…”
Section: Overview Of Simulationsmentioning
confidence: 60%
“…In our simulations, reionization completes at higher redshifts than suggested by constraints on the neutral fraction from observations of Lyman-α emitting galaxies and high-redshift quasars (e.g., Figure 5 in Robertson et al 2013). However, interpretations of these observations are dominated by large systematic uncertainties (for a discussion see, e.g., Robertson et al 2013;Jensen et al 2013;Dijkstra 2014;Mesinger et al 2014;Taylor & Lidz 2014).…”
Section: Overview Of Simulationsmentioning
confidence: 60%
“…There has been some controversy in the literature about the shape of the SFRD at high redshifts (e.g., Robertson et al 2013;Oesch et al 2015), reflected by the wide range in estimated star formation rates at higher redshifts shown by the data points in Fig. 7.…”
Section: Predictions For High-redshift Galaxy Observationsmentioning
confidence: 99%
“…At the same time, the first stars and galaxies were forming from primordial gas clouds in the Universe. Although there is a clear connection between these two events (Barkana & Loeb 2001;Bromm & Yoshida 2011;Loeb & Furlanetto 2013;Robertson et al 2013), their detailed relation is unknown, thanks to uncertainties in the properties of the galaxy populations. Fortunately, understanding the epoch of reionization itself will also shed light on the formation and evolution of early galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…The escape fraction is a key parameter in studies of the contribution of the observed galaxy population to reionization (e.g. Bouwens et al 2012;Robertson et al 2013), semi-analytic modelling of reionization (e.g. Choudhury et al 2009;Pritchard et al 2010;Santos et al 2010;Mesinger et al 2011;Raskutti et al 2012;Mitra et al 2013;Shull et al 2012) and numerical simulations of reionization (e.g.…”
Section: Introductionmentioning
confidence: 99%